Synthesis, Characterization and Antimicrobial Activity of V(IV) and Mo(VI) Complexes of Hydrazones - Pradhan, Alka; Dubey, Neelam; Sharma, Vandana; Nair, Usha; Chandrayan, Alok (Asian Journal of Chemistry, 2010)
Some new biologically active hydrazone complexes of V(IV) and Mo(VI) have been synthesized and characterized by IR and elemental analyses. The biological screening was done against two pathogenic bacteria, i.e., Klebsiella and Pseudomonas and two nonpathogenic bacteria, i.e., Escherichia coli and Staphylococcus aureus in order to explore their potential antimicrobial activities.